Deformation and bending strength of high‐performance lead‐free piezoceramics. Issue 5 (18th January 2022) - Lalitha, K. V.; Isaia, Daniel; Gong, Wen; Wu, Chaofeng; Li, Yingwei; Rödel, Jürgen
Abstract: Bending strength of commercially relevant lead‐free piezoceramics – 0.935Na0.5 Bi0.5 TiO3 ‐0.065BaTiO3 (NBT‐6.5BT) with and without acceptor Zn‐doping and 0.92(K0.5 Na0.5 )NbO3 ‐0.02(Bi0.5 Li0.5 )TiO3 ‐ x BaZrO3; x  = 0.06, 0.07 (KNN‐BZ 100x ) have been quantified using 4‐point bending tests and contrasted to that of commercial lead zirconate titanate (PZT, PIC151). The compressive and tensile strength probed using additional strain gauges under 4‐point bending indicate negligible non‐linear deformation, in stark contrast to that of commercial PIC151. The bending strength of KNN‐BZ 100x is about 100 MPa, comparable to PIC151, while that of NBT‐6.5BT‐based materials is about twice that of PIC151 at ∼160 MPa. These results are rationalized based on the intrinsic characteristics of the lead‐free piezoceramics in terms of fracture toughness, coercive stress, and Young's modulus. Weibull statistics indicate a higher fracture probability for KNN‐based materials, with NBT‐6.5BT‐based materials featuring Weibull modulus twice that of KNN‐based materials.